Theoretical Framework for Migration Research - Jnawali, Damodar (The Third Pole: Journal of Geography Education, 2014)
Migration is a spatial or geographical mobility of human population. Present paper deals with the concept of theoretical and conceptual framework in a research with specific reference to migration studies. A theory provides guidelines for a research work whereas conceptual framework is based on a theory or it is a modified model of the previous researchers that can be developed according to the nature of present research proposed. The researcher has to identify variables affecting migration and develop hypotheses in order to establish relationship between dependent and independent variables to be used in the study. DOI: http://dx.doi.org/10.3126/ttp.v11i0.11522 The Third Pole Vol. 11-12, 2012 page: 1-5